Exploring geothermal energy as a sustainable source of energy: A systemic review - Charity M. Nkinyam; Chika Oliver Ujah; Christian O. Asadu; Daramy V.V. Kallon (Unconventional Resources)
Geothermal energy is a renewable energy source with potential to facilitate the world's transition to clean and sustainable energy. Despite its capabilities, geothermal energy currently accounts for barely 0.34 % of the global energy contribution. However, its ability to provide consistent and reliable electrical power especially for base load demand positions it as a competitive alternative to fossil fuels. The installed capacity of geothermal generation has increased from 9791 MWe in 2009 to 16,318 MWe by the end of 2023, with over 32 countries actively developing their geothermal resources. An in-depth literature review explores the evolution of geothermal energy as a clean energy option, illustrating its significant impact and the challenges it faces. To enhance its competitiveness relative to fossil fuels, which benefit from established support and subsidies, geothermal energy requires government backing in the form of favorable feed-in tariffs and preferential tax treatment. This review emphasizes geothermal energy's potential, extraction technologies, geothermal power plants, geothermal applications, and areas for further research. Additionally, it outlines current research initiatives and provides recommendations for stakeholders to promote geothermal energy as a vital component of a clean energy future.